Palavra, voz e imagem: a poética de Arnaldo Antunes - Lopes, Márcia Plana Souza (2007)
The present dissertation has as objective to elaborate a reflection on the poetical of Arnaldo Antunes, developed in the multimedia processes. The reason of the choice of the dimensions - word, voice and image - of his poetry as object of study, due to the fact of his wide cultural artistic dimension in workmanships provide to the poetry in the computing society. Questions had been raised in the attempt to apprehend the construction of that contemporary poetic. It is asked: How does the poetical proposal of Arnaldo Antunes, operating the multimedia process of visual, sonorous, image able and sensorial artistic language, reflect in literature? How does the reading of the verbal vocal visual and haptic signs deny the structure of the literary gender? Focusing on the problematic points and the objectives, it was arisen as hypotheses: The poetry of Arnaldo Antunes operates in the border of codes and languages, resulting in new poetical speech; it holds, also, diverse artistic codes and other areas of the knowledge, recreating the form to make poetry, by means of a hybrid and multimedia language. The poem selection argues counterpoint between the voice and silence, the symmetry of the languages in the search of the other, the thing as a concise concrete material in itself, the revelation of the intercrossing between space and time. The theoretical base that guides this work is mainly studies of authors as August De Campos, Décio Pignatari, E.E. Melo and Castro, Edgard Braga, Haroldo De Campos. Among others conclusions, it is apprehended a poetical in constant transit; arnaldianas poetical experiences that reveal a kind of anti gender; a poetry that appropriates of the cultural hybridization and the inter arts, contributing to solidify a new form of poetry in the contemporary context